Sintasan dan Pertumbuhan Benih Pasca Larva Beberapa Subspesies Gurami (Osphronemus goramy) - Dewi N. Setyowati; Ign. Hardaningsih; Susilo B. Priyono (Jurnal Perikanan Universitas Gadjah Mada, 2007)
The objective of this research was to know the survival and growth of post-larvae of several giant gouramy (Osphronemus goramy) subspecies. Experiment in this study used Completely Randomized Design (CRD). The treatment consisted of three strains of giant gouramy, bastar, bluesafir, and bule. Giant gouramy post-larvae were reared for 45 days. The results showed that there were no significantly different among those subspesies of giant gouramy (P>0,05) on survival rate (bastar=86,5%; bluesafir=61,5%; bule=87,0%), weight and length (bastar=0.946 g, 2.975 cm; bluesafir=0.585 g, 2.860 cm; bule=0.826 g, 3.280 cm), also on the specific growth rate of length (bastar=3,070%/day, bluesafir=2,891%/day, bule=3,308%/day). However there was significantly different on specific growth rate of weight (P<0,05) (bastar=7,356%/day, bluesafir=9,464%/day; bule=11,167%/day).